Contemporary Management of Vesico-Urethral Anastomotic Stenosis After Radical Prostatectomy - Rosenbaum, Clemens M.; Fisch, Margit; Vetterlein, Malte W. (Frontiers in Surgery, 2020)
Vesico-urethral anastomotic stenosis is a well-known sequela after radical prostatectomy for prostate cancer and has significant impact on quality of life. This review aims to summarize contemporary therapeutical approaches and to give an overview of the available evidence regarding endoscopic interventions and open reconstruction. Initial treatment may include dilation, incision or transurethral resection. In treatment-refractory stenoses, open reconstruction via an abdominal (retropubic), perineal or combined abdominoperineal approach is a viable option with high success rates. All of the open surgical procedures are generally accompanied by a high risk of developing de novo incontinence and patients may need further interventions. In such cases, subsequent artificial urinary sphincter implantation is the most common treatment option with the best available evidence.